(untitled) (Research, Society and Development, 2022)
Bodies are born implied by culture, they are born determined by ingrained discursive technologies that will define the most appropriate ways of making genres. In a country that structurally presents the most diverse prejudices, such as race, class and gender, transphobia is configured in various ways in the social spheres, either by neglecting or violating basic rights for the trans population. This article is a part of the results of the research carried out during the doctorate and aims to discuss the body and its implications on the construction of gender identity, based on the dialogues of the author of this with transsexuals and transvestites in Maceió. These reports took place at the time of immersion in the field, when I started the research in 2018 The qualitative investigation resorted to bibliographic and empirical research, through observation and open interview techniques, and to analyze the data, the discourse analysis based on Pêcheux (1995) and Orlandi (2001; 2007) was used.In its first part, it addresses gender, gender identity and sexual orientation, then discusses trans bodies as political bodies. Discusses trans identity and its idiosyncrasies. Finally, it discusses the struggle of transsexuals in the construction of their identity. From the reflections brought, it is evident how political trans bodies are, being these involved in the already conceived understandings of gender, gender identity and sexual orientation from such an excluding perspective, revealing the importance of the discourses that we (re)produce about these identities and how this can affect these realities.